Nazwy zależnościowe na -ycz, -owycz/-ewycz* w systemie antroponimicznym ukraińskiego stanu uprzywilejowanego w XV–XVII wieku - Mytnik, Irena (Slavia Orientalis, 2025)
The purpose of the article is to identify and describe the function of the paternal formations in -ycz, -owycz/-ewycz* and their participation within the anthroponymic system of privileged social status in Ukraine in the 15th–17th centuries. The analyses carried out revealed three functions of the patronyms in question: the function of historical names, dependency names indicating the current father-son relationship, and the function of nicknames. They occupied a very important place in the naming system, with their tradition dating back to the early Middle Ages, while their functioning had no social restrictions. They constituted the second largest group of post-name terms, second only to historical misnomers, on which the identification of the social status in question was based. Current patronymics derived from paternal names mostly occurred in three-element formulas, and their functioning was also embedded in tradition. Combinations of this type in bourgeois and peasant anthroponymy were just occasional. Anthroponyms with the formants in question also occurred as dynastic epithets, commemorating the progenitors of families, individual and single-generation family names, constituting a kind of privilege for princes and nobility.